COMMUNICATION STRATEGIES USED BY 2nd SEMESTERSTUDENTS OF ENGLISH STUDY PROGRAM IN UNIVERSITAS BRAWIJAYA WITH DIFFERENT ANXIETY LEVELS IN TELLING COMIC STRIPS - CRISILLA, SYAILENDRA YUDA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Yuda Crisilla, Syailendra. 2013. Communication Strategies Used by 2 Semester Students of English Study Program in Universitas Brawijaya with Different Anxiety Levels in Telling Comic Strips. Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, Universitas Brawijaya.Supervisor: Fatimah; Co-supervisor: Didik HartonoKeywords: communication strategies, anxiety, anxiety levels, foreign languagelearning.Students usually face some problems in speaking a foreign language. To overcome the problems, they have certain ways that are called as communication strategies. Anxiety as an affective factor can influence the students in using communication strategies. In this study, the writer conducted a study on communication strategies used by 2nd semester students of English Study Program in Universitas Brawijaya with different anxiety levels in telling comic strips. The writer uses theory of communication strategies by Dörney (1995) . There are two problems of the study which were proposed: (1) What are the types of communication strategies used by students with high and low anxiety level when telling the comic strips (2) How is the frequency of types of communication strategies used by students with low and high anxiety level when telling the comic strips.This study used qualitative approach in relation to the use of clear and systematic description about the phenomena being studied. There were 16subjects in this study. They came from Academic Speaking Class students who were selected using FLCAS that is developed by Horwitz et al. (1986) and dividedinto two groups, namely subjects with high and low anxiety level. The data wereutterances containing communication strategies in telling comic strips.This study reveals that there are 13 types of communication strategies usedby subjects with high anxiety level. On the other hand, subjects with low anxietylevel used 15 types of communication strategies. The writer also found that thefrequency of the communication strategies used by subjects with high and lowanxiety were different. Subjects with high anxiety level produced higher numberof communication strategies than subjects with low anxiety level. The writer alsoconcludes that the more anxious students tend to produce less effective ofcommunication strategies than those who feel relaxed in speaking. The writer suggests foreign language teacher find an appropriate teaching method to manage the students’ anxiety and introduce communication strategies in speaking class. The writer also suggests to the next researchers to conduct moreresearch about communication strategies with other theories and also differentvariables.